Obesity, inflammation, and insulin resistance - Luana Mota Martins; Ana Raquel Soares Oliveira; Kyria Jayanne Clímaco Cruz; Francisco Leonardo Torres-Leal; Dilina do Nascimento Marreiro (Brazilian Journal of Pharmaceutical Sciences, 2014)
White adipose tissue (WAT) is considered an endocrine organ. When present in excess, WAT can influence metabolism via biologically active molecules. Following unregulated production of such molecules, adipose tissue dysfunction results, contributing to complications associated with obesity. Previous studies have implicated pro- and anti-inflammatory substances in the regulation of inflammatory response and in the development of insulin resistance. In obese individuals, pro-inflammatory molecules produced by adipose tissue contribute to the development of insulin resistance and increased risk of cardiovascular disease. On the other hand, the molecules with anti-inflammatory action, that have been associated with the improvement of insulin sensitivity, have your decreased production. Imbalance of these substances contributes significantly to metabolic disorders found in obese individuals. The current review aims to provide updated information regarding the activity of biomolecules produced by WAT.